JAK/STAT signaling in regulation of innate lymphoid cells: The gods before the guardians. Issue 1 (7th October 2018) - Stabile, Helena; Scarno, Gianluca; Fionda, Cinzia; Gismondi, Angela; Santoni, Angela; Gadina, Massimo; Sciumè, Giuseppe
Summary: Immunity to pathogens is ensured through integration of early responses mediated by innate cells and late effector functions taking place after terminal differentiation of adaptive lymphocytes. In this context, innate lymphoid cells (ILCs) and adaptive T cells represent a clear example of how prototypical effector functions, including polarized expression of cytokines and/or cytotoxic activity, can occur with overlapping modalities but different timing. The ability of ILCs to provide early protection relies on their poised epigenetic state, which determines their propensity to quickly respond to cytokines and to activate specific patterns of signal‐dependent transcription factors. Cytokines activating the Janus kinases (JAKs) and members of the signal transducer and activator of transcription (STAT) pathway are key regulators of lymphoid development and sustain the processes underlying T‐cell activation and differentiation. The role of the JAK/STAT pathway has been recently extended to several aspects of ILC biology. Here, we discuss how JAK/STAT signals affect ILC development and effector functions in the context of immune responses, highlighting the molecular mechanisms involved in regulation of gene expression as well as the potential of targeting the JAK/STAT pathway in inflammatory pathologies.